2018
DOI: 10.1037/aap0000097
|View full text |Cite
|
Sign up to set email alerts
|

Bilinear and multidimensional cultural orientations and indigenous family process among Korean immigrant mothers and fathers.

Abstract: This study examined how parental cultural orientations and family process are related among Korean immigrant parents (272 mothers, and 164 fathers, N=436) and how the relationship varies across fathers and mothers. Multiple scales were used to assess bilinear, multidimensional cultural orientation towards both the culture of origin and mainstream culture. The dimensions of language, identity, and cultural participation as well as the number of years living in U.S. were analyzed. The main findings include: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
1
9
1
Order By: Relevance
“…We in fact included several acculturation variables in the earlier versions. However, similar to the findings of existing studies (Choi et al, 2018; Choi et al, 2013), we found that acculturation measured by language, identity, and the number of years living in the United States was largely not associated with AA family process. Further, a high number of predictors posed challenges in interpretations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We in fact included several acculturation variables in the earlier versions. However, similar to the findings of existing studies (Choi et al, 2018; Choi et al, 2013), we found that acculturation measured by language, identity, and the number of years living in the United States was largely not associated with AA family process. Further, a high number of predictors posed challenges in interpretations.…”
Section: Discussionsupporting
confidence: 91%
“…It is imperative to correctly guide AA families to construct parenting values and behaviors that can establish positive parent–child relations and help youth development. Culturally unique parenting and parent–child relationships persevere (Choi et al, 2018), and it is a common struggle among AA parents to balance traditional parenting and acculturative pressure. KA parents tend to experience language barriers unlike FA parents, which is likely to add challenges in parenting and parent–child relationships.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, minority groups have been found to be more likely to adopt the behavioral norms of the dominant culture more readily than the values of the dominant culture (Rosenthal & Feldman, 1992). This finding was later affirmed with Asian American populations (Choi et al, 2018). In the present study, three distinct dimensions of cultural orientation are used in generating acculturation strategies: language competency, strength of identity, and behavioral cultural participation within host culture versus heritage culture (Choi et al, 2016; Ward, 2001).…”
Section: Introductionmentioning
confidence: 73%
“…In support, the research on Asian immigrant parenting found that acculturation was related to authoritative parenting, parental warmth, inductive reasoning, and less punitive parenting, while enculturation was related to authoritarian parenting, less inductive reasoning, and more punitive parenting (Cheah et al, 2018; Kim et al, 2014; Vu et al, 2019; Yu et al, 2016). In addition, even if the core traits of parenting (e.g., centrality of family) persist, specific practices may vary by cultural orientations (Choi, et al, 2018).…”
Section: Acculturation/enculturation and Parenting Practicesmentioning
confidence: 99%